Reliability of Telepsychiatry Assessments Using the Attention-Deficit/Hyperactivity Disorder Rating Scale-IV for Children With Neurodevelopmental Disorders and Their Caregivers: Randomized Feasibility Study - Kurokawa, Shunya; Nomura, Kensuke; Hosogane, Nana; Nagasawa, Takashi; Kawade, Yuko; Matsumoto, Yu; Morinaga, Shuichi; Kaise, Yuriko; Higuchi, Ayana; Goto, Akiko; Inada, Naoko; Kodaira, Masaki; et al. (Journal of medical Internet research, 2024)
Given the global shortage of child psychiatrists and barriers to specialized care, remote assessment is a promising alternative for diagnosing and managing attention-deficit/hyperactivity disorder (ADHD). However, only a few studies have validated the accuracy and acceptability of these remote methods. This study aimed to test the agreement between remote and face-to-face assessments. Patients aged between 6 and 17 years with confirmed Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition diagnoses of ADHD or autism spectrum disorder (ASD) were recruited from multiple institutions. In a randomized order, participants underwent 2 evaluations, face-to-face and remotely, with distinct evaluators administering the ADHD Rating Scale-IV (ADHD-RS-IV). Intraclass correlation coefficient (ICC) was used to assess the reliability of face-to-face and remote assessments. The participants included 74 Japanese children aged between 6 and 16 years who were primarily diagnosed with ADHD (43/74, 58%) or ASD (31/74, 42%). A total of 22 (30%) children were diagnosed with both conditions. The ADHD-RS-IV ICCs between face-to-face and remote assessments showed "substantial" agreement in the total ADHD-RS-IV score (ICC=0.769, 95% CI 0.654-0.849; P<.001) according to the Landis and Koch criteria. The ICC in patients with ADHD showed "almost perfect" agreement (ICC=0.816, 95% CI 0.683-0.897; P<.001), whereas in patients with ASD, it showed "substantial" agreement (ICC=0.674, 95% CI 0.420-0.831; P<.001), indicating the high reliability of both methods across both conditions. Our study validated the feasibility and reliability of remote ADHD testing, which has potential benefits such as reduced hospital visits and time-saving effects. Our results highlight the potential of telemedicine in resource-limited areas, clinical trials, and treatment evaluations, necessitating further studies to explore its broader application. UMIN Clinical Trials Registry UMIN000039860; http://tinyurl.com/yp34x6kh.